Presidents and intermediaries: insights from clean energy policy processes in Mexico - Solorio Sandoval, Israel; Tosun, Jale (Policy studies, 2023)
We assess whether different presidents have different “styles” of involving intermediary organizations such as trade unions or business associations in the policy process. Given that temporal variation in the relationship between presidents and intermediaries can be observed, to what extent can the intermediaries included in the policy process be explained by the respective president’s leadership style and/or political ideology? We concentrate on the process by which clean energy policies were formulated under three Mexican presidents between 2006 and 2022. We draw on original data collected through 18 semi-structured interviews carried out with intermediaries between January and July 2022. Our findings show that the different presidents had different policy styles and therefore varied in how they included climate intermediaries in the policy process. This finding has important implications for research on policy styles as well as climate intermediation. Regarding policy styles the results presented call for theorizing of the dynamics observed. As concerns climate intermediaries the corresponding literature is invited to pay more attention to the political context in which they operate.
Online veröffentlicht: 29 Nov 2022
Gesehen am 29.07.2024